on expanding polynomial (6x^2−11y^3)(−6x^2−11y^3) or [tex](6x^2-11y^3)(-6x^2-11y^3)[/tex] is [tex]121y^6 -36x^4[/tex] .
Step-by-step explanation:
We have , (6x^2−11y^3)(−6x^2−11y^3):
[tex](6x^2-11y^3)(-6x^2-11y^3)[/tex]
⇒ [tex](6x^2-11y^3)(-6x^2-11y^3)[/tex]
We know that :
[tex](a +b)(c+d) = (ac+ad+ad+bd)[/tex]
⇒ [tex](6x^2(-6x^2) - 11y^3(-6x^2) )+(6x^2(-11y^3) + (-11y^3)(-11y^3))[/tex]
⇒ [tex](-36x^4+66x^2y^3 -66x^2y^3 + 121y^6)[/tex]
⇒ [tex](-36x^4+ 121y^6)[/tex]
⇒ [tex]121y^6 -36x^4[/tex]
Therefore, on expanding polynomial (6x^2−11y^3)(−6x^2−11y^3) or [tex](6x^2-11y^3)(-6x^2-11y^3)[/tex] is [tex]121y^6 -36x^4[/tex] .